Ecologia populacional e reprodutiva de Macrobrachium amazonicum (Heller, 1862) (Decapoda: Palaemonidae) no reservatório da Usina Hidrelétrica de Miranda, Rio Araguari, MG - Silva, Raquel Costa e (2014)
The palaemonid shrimp Macrobrachium amazonicum is widely distributed in coastal rivers, estuaries and inland waters of South America, despite this, little is known regarding its biology in the natural environment. Furthermore, there is a scarcity of studies related to this species in rivers and reservoirs in the State of Minas Gerais. Considering this, the present study aimed to analyze aspects of population and reproductive ecology of M. amazonicum. Sampling was carried out monthly from April/12 to May/13 (except in May/12) in Miranda Hydroelectric Reservoir situated at Araguari River - MG (19º 03 13,0 S / 047º 59 25,5 W), using hand sieves. The water temperature was measured in each sampling. Data referring to rainfall were obtained from the Laboratory of Climatology and Hydric Resources of the Institute of Geography at UFU. The sampled specimens were identified, sexed and measured. For the determination of fecundity, after removing the egg mass, the eggs were counted under a stereoscopic microscope. Size and volume of eggs were determined for the three stages of development. A total of 2584 specimens were analyzed, corresponding to 1668 females (1417 juveniles, 149 adults non-ovigerous and 102 ovigerous), 755 males (745 juveniles and 10 adults) and 161 sexually undifferentiated shrimps. The sex ratio differed significantly in favor of females and they were statistically larger than males. The length-frequency distribution of the specimens revealed an unimodal pattern, with peaks of occurrence in 4.0 4.9 mm class for males and 3.0 3.9 mm class for females. First maturation length (carapace length) for both sexes resulted in 6.3 mm. Reproduction in M. amazonicum was continuous with a gradual increase from April to June/12. No significant relationship between the frequency of ovigerous females and the environmental variables was observed. The fecundity showed a positive linear relation with the carapace length and the number of eggs varied from 33 to 389 eggs/female, totaling 11.775 eggs. Recruitment was continuous with a gradual increase during the months of November and December/12, besides April and May/13. There was an increase in the size/volume of eggs from early to late embryonic stage. Ovigerous females produced eggs at the same development stage with the same size and volume regardless of their body size. Our results demonstrated higher similarity to other continental M. amazonicum populations than from estuarine ones, showing the environment influence in the life-history of individuals. This study is also a contribution to the biology of M. amazonicum in natural environment, in addition to being one of the few already carried out in Minas Gerais on this species of great ecological importance.